Risk when buying food by e-commerce: what factors influence the consumer's perception of risk? - Villalobos Monge, Alexis (2021)
Risk is a key aspect to be considered whenanalysing economic decisions. This investigation is one of the first to review the risk that a person perceives when making the decision to buy food using electronic commerce as their purchase channel. It was possible to determine that convenience associated with ease of use and hedonic motivations represent the impulses with the greatest influence on this perception. A virtual food shopping experiment was conducted for 30 weeks, and 223 responses were obtained from shoppers with different demographic characteristics. The results were modelled through variance analysis where statistically significant differences were found (p-value <0,05) for exogenous and endogenous variables. It was determined, among other findings, that the perception of risk in the virtual purchase of food is lower compared to other purchase channels such as supermarkets and farmer’s markets.